Purifying radioactively contaminated groundwater using lead-modified activated charcoal - Saad M. El-Said; Mahmoud Roushdi (Water Science)
Groundwater is a vital source of potable water worldwide. However, contamination by radionuclides and heavy metals, originating from natural and industrial sources, poses significant risks to humans, animals, and plants. This study focuses on the purification of radioactively contaminated groundwater using lead-modified activated charcoal. The charcoal was synthesized by incorporating lead ions from a lead acetate solution into the crystal lattice of activated charcoal under controlled carbonization conditions, varying temperature, and lead acetate concentrations. Tectanium-99 (beta rays) and pertectanium-m99 (gamma rays) were employed in experimental setups to simulate contamination. Comprehensive characterization of the lead-modified activated charcoal was conducted using SEM, FTIR, BET, and zeta potential analyses to elucidate its adsorption mechanism. Batch experiments assessed the removal efficiency of radiation from synthetically contaminated water, examining the effects of pH, contact time, and contaminant concentration. The results revealed that the lead-modified activated charcoal achieved up to 98% radiation removal using just 0.1 grams within 15 minutes at a pH of 3.0. Building on these promising results, the study progressed to a fixed-bed column setup, a practical solution for larger-scale applications. A dual-column system, packed with lead-modified activated charcoal, was designed to ensure complete radiation removal. The performance of the fixed-bed system was evaluated, focusing on flow rate and bed height. Optimal conditions for maximal radiation removal were determined to be a flow rate of 15 mL/min and a bed height of 15 cm. This research highlights the development of a novel, cost-effective material for purifying radioactively contaminated water and demonstrates the successful design of an adsorption column that maximizes the material’s efficiency for real-world applications.